INTEGRATED HOTEL OR PRIVATE ACCOMMODATION? - TOURISTS’ RESPONSES TO INNOVATIVE HOSPITALITY - Floričić, Tamara; Pavia, Nadia (Journal of Tourism, Sustainability and Well-being, 2018)
The main aim of this paper is to research the preferences of accommodation service users in regard to integration of private accommodation facilities often called private household accommodation into an integrated hotel. This innovative form of accommodation provides a higher level of service, which directly affects the competitiveness of a hospitality offer. A summarised literature review is presented in the paper and, as it concerns a modern problem area, it represents a new insight and contribution to new knowledge. In the paper, the results of the conducted empirical research are exposed and discussed. The research reveals that users of accommodation in apartments do not clearly recognise the new form of the innovative accommodation offer, its concept, facilities or services. The paper represents a valuable contribution to the research of tourists’ preferences for integrated hotels in comparison with private accommodation and points to the aspects which should be implemented.